Sara Angelucci: Provenance Unknown. ART GALLERY OF YORK UNIVERSITY, TORONTO. - Sadinsky, Elana (Archivaria, 2013)
Sara Angelucci: Provenance Unknown. ART GALLERY OF YORK UNIVERSITY, TORONTO. Mounted at the Art Gallery of York University, 10 April–16 June 2013.